Políticas públicas habitacionais brasileiras e direito fundamental à moradia: interfaces e confrontações - Lima, Filipe José Vilarim da Cunha (2013)
This thesis covers the need to accomplish the fundamental right to property. Therefore, its main goal consists on the role of the State, as the agent responsible for the implementation of the project development by the Federal Constitution of 1988, under which it is contemplated the right to property; task to be undertaken through the implementation of public policies. To achieve its objectives, the method of deductive approach will be used, as well as the analytical, historical and interpretive methods, throughout bibliographic and documental researches. This work will examine the relationship between the should be normative and the social and political be , checking the determinant reasons for the lack of constitutional norms implementation, which enshrine the social rights and establishes the need for positive, constant and progressive state action to achieve these rights . It will also be equally addressed, the national and international legal framework of the right to property , as well as policy instruments established under the Brazilian Law for the materialization of this right. To sum it up, the Brazilian housing policies will be faced and developed by the Brazilian State, focusing on its positive and negative aspects, in order to analyze the exclusion reasons of the low-income beneficiaries from the spectrum of the State actions, based on the necessary assumptions to meet the housing deficit in this population layer.